(untitled) (Journal of Applied Oral Science, 2021)
Gap formation of composite resin restorations is a serious shortcoming in clinical practice. Polymerization shrinkage stress exceeds the tooth-restoration bond strength, and it causes bacterial infiltration within gaps between cavity walls and the restorative material. Thus, an intermediate liner application with a low elastic modulus has been advised to minimize polymerization shrinkage as well as gap formation. Objective: The purpose of this in vitro study was to assess gap formation volume in premolars restored with different bulk-fill composites, with and without a resin-modified glass-ionomer cement (RMGIC) liner, using x-ray micro-computed tomography (micro-CT). Methodology: Sixty extracted human maxillary premolars were divided into six groups according to bucco-palatal dimensions (n=10). Standardized Class II mesio-occluso-distal cavities were prepared. G-Premio Bond (GC Corp., Japan) was applied in the selective-etch mode. Teeth were restored with high-viscosity (Filtek Bulk Fill, 3M ESPE, USA)-FB, sonic-activated (SonicFill 2, Kerr, USA)-SF and low viscosity (Estelite Bulk Fill Flow, Tokuyama, Japan)-EB bulk-fill composites, with and without a liner (Ionoseal, Voco GmbH, Germany)-L. The specimens were subjected to 10,000 thermocycles (5-55°C) and 50,000 simulated chewing cycles (100 N). Gap formation based on the volume of black spaces at the tooth-restoration interface was quantified in mm3 using micro-computed tomography (SkyScan, Belgium), and analyses were performed. Data were analyzed using repeated-measures ANOVA and the Bonferroni correction test (p < 0.05). Results: The gap volume of all tested bulk-fill composites demonstrated that Group SF (1.581±0.773) had significantly higher values than Group EB (0.717±0.679). Regarding the use of a liner, a significant reduction in gap formation volume was observed only in Group SFL (0.927±0.630) compared with Group SF (1.581±0.773). Conclusion: It can be concluded that different types of bulk-fill composite resins affected gap formation volume. Low-viscosity bulk-fill composites exhibited better adaptation to cavity walls and less gap formation than did sonic-activated bulk-fill composites. The use of an RMGIC liner produced a significant reduction in gap formation volume for sonic-activated bulk-fill composites.